(untitled) (Acta Scientiarum. Health Sciences, 2012)
Nervous System Mobilization is used to restore the biomechanics of the nervous system and adjacent structures, promoting the return to their duties. This study evaluated the pain threshold to pressure, to cold, and the cold pain intensity in healthy subjects that underwent intervention with neural mobilization. The sample consisted of 20 volunteers with a mean age of 19.5 ± 1.0 years. The participants were divided randomly into two groups: group 1 (G1) and group 2 (G2); the first group received intervention by means of neural mobilization, and the second, by means of conventional stretching exercises, on the first day; on the subsequent day the procedures were reversed for the groups. The volunteers were evaluated using the pain threshold to pressure and to cold, and the cold pain intensity, prior, immediately after, 20, and 40 minutes after the intervention. No significant differences were found between any assessments. In conclusion, the pain threshold to pressure and to cold, and the cold pain intensity had no significantly change after neural mobilization.